Analyzing Gen Z's Interest in Paying Zakat on Digital Platforms - Hanifatuz Zulva Oktavia Al Hasani; Trischa Relanda Putra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The rise of digital wallets in society, especially the millennial generation, has driven the concept of a cashless society where individuals use online transaction activities instead of physical cash for financial transactions. Gen Z has the potential to contribute to expanding Zakat acquisitions in Indonesia with online payments. This convenience can influence Gen Z's interest in paying zakat via digital platforms. The research method used is a quantitative method with a survey approach, with multiple linear regression analysis techniques. This research uses a purposive sampling technique with primary data originating from questionnaires distributed to the respondents' criteria in the research. The research results show that the image of the institution (X1) and convenience (X3) influence the interest in paying zakat through digital zakat among Gen Z in Gresik Regency. Zakat literacy (X2) does not influence interest in paying zakat via digital zakat among Gen Z in the Gresik Regency.